Requirements for the culture of the Pacific white shrimp, Litopenaeus vannamei, reared in low salinity waters: water modification and nutritional strategies for improving production - A. Roy, Luke; Allen Davis, D. (Facultad de Ciencias Biologicas, 2010)
The culture of shrimp utilizing low salinity water (LSW) has become common practice in a number of countries worldwide. The Pacific white shrimp, Litopenaeus vannamei, is the preferred shrimp species for culture in LSW, primarily due to its remarkable ability to effectively grow and survive at extreme salinities. In the last decade, significant strides have been made in the understanding of low salinity culture of this particular species. Improved understanding of the physiology of L. vannamei has translated into the development of effective culture techniques that have resulted in profits for farmers utilizing LSW. In general, two separate strategies have been employed by researchers to improve growth and survival of L. vannamei reared in LSW. These strategies include water modification approaches which alter the low salinity rearing medium to make it more acceptable for production of shrimp and nutritional strategies that focus on modification of diets offered to shrimp, usually with supplements that might theoretically improve osmoregulatory capacity. This article seeks to summarize research findings from both of these approaches and ultimately provide a recommendation to shrimp farmers using LSW as a rearing medium for the culture of L. vannamei.